KO-SENSITISASI XANTOFIL PADA SISTEM SEL SURYA TERSENSITISASI KLOROFILIN - , LINDA DWITASARI, Dr.Indriana Kartini, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Dye-sensitized solar cell using chlorophyllin (C), xanthophylls (X), and the mixture of two pigments as the sensitizer have been studied. This research investigated the spectral absorption of the chlorophyllin and xanthophyll mixture in solution, the dyes capability of sensitizing TiO2 surfaces, and comparing the DSSCâs efisieciency using blended dyes as well as single dyes of chlorophyllin and xanthophylls as the sensitizer. Chlorophyll extract of spinach powder was hydrolysed with 7% KOH in methanol. Xanthophyll was extracted from fresh petal chrysanthemum with mixed solvent of absolute ethanol:petroleum eter (60:40). The dyes was blended at various volume ratios of (C:X) 1:0, 5:1, 1:1, 1:5, and 0:1. The sensitization ability of the dyes were analyzed by comparing the absorption of the dyes in solution with the absorption of adsorbed dyes on TiO2 surfaces. While cyclic voltammetry with ITO/TiO2-dyes as the electrode was used to estimate the oxidation potential of the dyes in order to calculate the HOMO and LUMO energy of the sensitizer. The cell efficiency was determined using I-V instrument in sandwich system FTO/TiO2- dyes as photoanode, FTO/platinum as cathode, and electrolyte redox of IË/I3Ë. The absorption spectra of the blending dyes shows no broadening absorption to longer wavelength. It is due to the near position of absorption peak between chlorophyllin and xanthophyll so it might be overlapped. The dye sensitization in TiO2 surface shows that the dyes are capable to sensitize TiO2 via aggregation effect. The I-V test confirmed that the energy conversion efficiency of the cosensitized natural dyes (C:X=1:5) resulted higher efficiency (10.5x10-3%) than that of single dyes of chlorophyllin and xanthophyll which is 2.23x10-3% and 7.3x10- 3%, respectively. The higher efficiency of co-sensitized dyes of chlorophyllin and xanthophyll probably based on their role of natural photosynthesis mechanism. Keyword:Co-sensitization, chlorophyllin, xanthophyll, DSSC